(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the article, the author made an attempt to study certain aspects of the activities of foreign non-governmental organizations in Kyrgyzstan. Along with this, educational projects and programs implemented in recent years by american, german and arab non-governmental organizations, which have a positive effect on the educational sector of the Kyrgyz Republic, have been analyzed.